IJCM_212A: Assessment of Effective Vaccine Management in Government Health Facilities of Jammu district - Chowdhary Nahida; Langer Bhavna; Gupta Rajiv K (Wolters Kluwer Medknow Publications, 2024)
Background: The success of immunization depends highly on the level of cold chain maintenance. For effective implementation and success of the Universal Immunisation Programme, proper maintenance of Cold Chain needs a great focus. In 2010, WHO and UNICEF launched the Effective Vaccine Management (EVM) initiative. EVM is a tool which assesses immunization supply chain logistics management. Objectives: To evaluate the performance of Immunization supply chain in cold chain points of Government Health Facilities (HF) of Jammu district Methodology: A facility based cross-sectional study was conducted in Jammu district of UT of J&K. The assessment was done during November 2021- October 2022 using WHO-UNICEF EVM assessment standalone questionnaire generated on EVM assessor app. Sample size and site selection were done using the WHO EVM site selection tool(v1.7-March 2014). A total of 31 HFs were assessed including Divisional Vaccine Store (SN) Results: None of the health facilities reached the WHO recommended overall score of >80%. The criterion scores showed that Facility infrastructure and equipment (E4) and waste management (E9) for District Vaccine Store (LD) was 83% & 86%. Vaccine management (E8) score for SN level & Government Hospital was 88% & 82%. Rest of the CCPs scored less than 80% for all the criteria(E2-E9). The scores of distribution of vaccines and dry goods (E7) were very low for Primary Health Centres (PHC) and Health & Wellness Centres (H&WC) i.e., 39% and 25%. The scores for all the categories(C1-C6) for various CCPs were below 80%. Management criteria scores for supportive supervision(M3) was 0% for all CCP except LD &PHC Conclusion: The overall performance of cold chain in Jammu district was below the recommended level. Supportive supervision, provision of safe disposal pits, power backup, micro plan, training of Cold Chain Handlers and provision of vaccine transportation facility can help in effective vaccine management